Pemanfaatan Kelobot Kering Sebagai Bahan Pembuatan Kertas - Ahmad Nur Syahid; Abdul Hadi Kadarusno; Iswanto Iswanto (Poltekkes Kemenkes Yogyakarta, 2014)
The increase of national corn production impacted to the increase of dry corn husk waste. The waste, if were not handled properly would cause environmental problems. Dry corn husk consist of 15,7 % lignin, 36,81 % cellulose, and 27,01 % lignecellulose, so that it can be used as mate-rial in paper making. The purpose of the study is to understand the influence of dry corn husk pulp variations on the pulling strength of the paper made, by conducted an experimental study which followed post-test only design. Five variations of the mass ratio of used paper pulp and dry corn husk pulp used in this study were: 1:0; 1:2; 1:2.5; 1:3; and 0:1; and were obeserved in nine replications. The results showed that the average of pulling strength of the paper yielded from above five ratio, respectively were: 2.030,02 grams; 7.004,06 gr; 9.038,37 gr; 11.888,78 gr; and 17.970,59 gr. Based on the results of the one way anova test, it was revealed that corn husk waste pulp determined the pulling strengh of the paper produced. The pulp waste only without used paper pulp addition earned the biggest pulling strength. The cellulose, lignin and hemicellu-lose content in dry corn husk were considered have function as an adhesive between the fibers and reinforce the bond and the length of the fibers. To conclude, the bigger the mass ratio be-tween corn husk pulp and used paper pulp, the higher the pulling strength will be gained.